MANAGEMENT OF TRACHOMATOUS CICATRICIAL ENTROPION OF THE UPPER EYE LID: OUR MODIFIED TECHNIQUE - Sadiq, Mohammad Naqaish; Pai, Anant (Journal of Ayub Medical College Abbottabad, 2005)
Background: Management of trachomatous cicatricial entropion of the upper eye lid presents a difficult problem. Many surgical approaches have been developed to address it. We report the functional and cosmetic results of our modified surgical technique we have developed in the management of trachomatous cicatricial entropion of the upper eye lid. Methods: 45 lids of 43 patients having trachomatous cicatricial entropion of upper eye lids were operated by our modified surgical technique in which we combine bilamellar tarsal margin rotation procedure with blepharoplasty. The technique and results were evaluated in a follow up period of up to 40 months. Results: In all 45 upper eye lids, the normal eyelashes rotated away from the surface of the eye and were no longer in contact of the eye ball in all position of gaze. All eyes had adequate lid closure and regular lid margin. No eye had any overhanging baggy fold of skin at operation site. Three eyes had conjuctival granuloma which was excised under local anaesthesia Three eyes needed Diode laser ablation to treat isolated cilia posterior to normal lash line. Three eyes had mild over correction which regressed without any surgical intervention. One lid had segmental necrosis of distal part of eye lid which recovered spontaneously in following days. Conclusion: Our modified technique of combining bilamellar tarsal rotation procedure (BTR) with blepharoplasty appears to be an effective surgical technique in the management of the trachomatous cicatricial entropion of the upper eye lid. It achieves successful anatomical correction along with more acceptable cosmetic appearance. Key words: trachomatous cicatricial entropion, bilamellar tarsal rotation, Blepharoplasty, Electrolysis, Cryotherapy